Preservation of reproductive material using the in vitro maturation method in patients with oncological diseases - Irina A. Lapina; Yulia E. Dobrokhotova; Iurii A. Sorokin; Anastasia A. Malakhova; Tatiana G. Chirvon; Vladislav V. Taranov; Natalya Iu. Germanovich; Eugenia V. Kovalskaya; Olesya V. Kaikova; Valeriia M. Gomzikova; Maria A. Tverdikova (IP Berlin A.V., 2022)
Background. Improving the quality of life of cancer patients is one of the priority tasks of the medical community. In the structure of oncological morbidity, the proportion of patients of fertile age accounts for up to 710% of all malignant neoplasms. About 30% of them have not realized their reproductive function by the time of the disease and need to preserve the genetic material due to the necessary gonadotoxic treatment. Taking into account the limited time before the start of surgery, as well as hormone-dependent variants of some tumors, the maturation of oocytes in vitro maturation (IVM) is a promising method. Aim. To evaluate the quantity and quality of oocytes obtained by IVM in a small sample of patients. Materials and methods. We conducted a prospective study, which included 5 patients of reproductive age. All patients were fully examined, the level of anti-muller hormone and the number of antral follicles were determined. After transvaginal puncture, oocytes were isolated and cultured from the obtained follicular fluid by embryologists in the laboratory for 56 days. Results. A total of 46 immature oocyte-cumulus complexes were obtained; 28 hours after oocyte culture in IVM medium, 30 (46%) oocytes at the metaphase II stage, 14 (22%) oocytes at the metaphase I stage and 12 (18%) oocytes at the prophase I stage were obtained. After additional cultivation, after 24 hours, another oocyte reached the metaphase II stage. As a result, 30 oocytes and 4 embryos were vitrified. Conclusion. The IVM method makes it possible to preserve the genetic material of patients with oncological diseases in a short time, without delaying the start of treatment with gonadotoxic therapy, allowing them to carry out their reproductive function in the future. Given the small number of studies and the lack of reliable protocols for using IVM, additional research in this area is needed.